The effect of training volume and intensity on competitive cyclists` efficiency - Hopker, J.; Coleman, D.; Passfield, L.; Wiles, J. (Applied Physiology, Nutrition, and Metabolism, 2010)
The impact of different intensity training on cycling efficiency in competitive cyclists is unknown. Twenty-nine endurance-trained competitive male cyclists completed 3 laboratory visits during a 12-week training period. At each visit, their cycling efficiency and maximal oxygen uptake were determined. After the first visit, cyclists were randomly split into 2 groups (A and B). Over the first 6 weeks, between tests 1 and 2, group A was prescribed specific high-intensity training sessions, whereas group B was restricted in the amount of intensive work undertaken. After test 2 and for the second 6-week period, group B was allowed to conduct high-intensity training. Gross efficiency (GE) increased in group A (+1.6 ± 1.4%; p < 0.05) following the high-intensity training, whereas no significant change was seen in group B (+0.1 ± 0.7%; p > 0.05). Group B cyclists increased their GE between tests 2 and 3 (+1.4 ± 0.8%; p < 0.05) but no changes in GE were observed in group A over this period (+0.4 ± 0.4%; p > 0.05). Delta efficiency (DE) did not change significantly in either group across the study period. This study demonstrates that GE is increased following high-intensity training in competitive male cyclists after 12 weeks.